Tackling 'grey hairs': How companies can turn an ageing workforce to their advantage - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2010)
The greying working population in developed economies will be widening intergenerational fissures in today’s companies and organisations. Young managers find it difficult to handle the 'grey hairs' under their charge, while older workers are not always happy taking orders from their younger supervisors. Yet, without talent, businesses run the risk of losing their competitiveness. How should companies bridge the gap and turn the skills and experience of their older workers into their advantage? Drawing examples and cases not just from America but also Singapore, Peter Cappelli and Bill Novelli, professors at Wharton and Georgetown respectively, share some ideas in the book “Managing the Older Worker”.